EXPORT OF RUSSIAN MANUFACTURES TO EU COUNTRIES: TENDENCIES, PROBLEMS AND OPPORTUNITIES - I. A. Korobkov (Vestnik MGIMO-Universiteta, 2013)
The modernization and specialization of the economy in hi-tech and high-value-added goods is the long term goal defined and set forward within the frame of Russian Federation 2020 Concept for the Social and Economic Development. According to the principles and clauses of the abovementioned document these high-tech and high-value-added products in the long run are intended to be exported to the European Union countries. For the foreseeable future EU will remain Russia’s key trade partner and moreover will play an immense and significant role for the integration of the Russian Federation in the international manufacturing and industrial processes. However, considering the high level of economic development of the EU countries and their strong positions in global exports of processed products including hi-tech goods, the export of the manufactures to the EU countries is quite a challenging task for Russia. Currently the manufactures that are supplied to the European Union mainly consist of semi-processed commodities, e.g., metals, diamonds and chemicals. Russian high-value-added products are exported to a limited number of partners; export volumes are comparatively moderate and volatile. However, some high-tech Russian products are successfully exported to the EU countries and meet growing demand from consumers from Central and Western Europe. The share of finished products and high-value-added goods exported to the Central and Eastern Europe slightly exceeds the EU average; the growing machinery and transport equipment sales are determined by an increased supply towards Poland, Slovakia, Bulgaria and Czech Republic.